2015
DOI: 10.1371/journal.pone.0133168
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Iron Deficiency in Guinea Pigs Increases Locomotor Activity but Does Not Influence Learning and Memory

Abstract: The objective of the current study was to determine whether prenatal iron deficiency induced during gestation in guinea pigs affected locomotor activity and learning and memory processes in the progeny. Dams were fed either iron-deficient anemic or iron-sufficient diets throughout gestation and lactation. After weaning, all pups were fed an iron-sufficient diet. On postnatal day 24 and 40, the pups’ locomotor activity was observed within an open-field test, and from postnatal day 25 to 40, their learning and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…An investigation into the effects of iron deficiency and iron deficiency anemia in young Zanzibari children demonstrated lower motor activity scores and less time in locomotion in affected children (54). However, there is evidence that early dietary iron deficiency can result in either reduced or increased locomotion (55, 56). To date, NCB5OR (or Cyb5R4) gene mutations have not been reported in patients with neurological diseases.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…An investigation into the effects of iron deficiency and iron deficiency anemia in young Zanzibari children demonstrated lower motor activity scores and less time in locomotion in affected children (54). However, there is evidence that early dietary iron deficiency can result in either reduced or increased locomotion (55, 56). To date, NCB5OR (or Cyb5R4) gene mutations have not been reported in patients with neurological diseases.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The weight difference became apparent starting from the third week of age and lasted until the end of the experiment, although iron deficiency treatment had ended at ~5 weeks of age. As we chose to group-house our piglets, we could not measure individual food intake, which ideally should be taken into account in nutritional studies that include growth performance as a read-oud parameter (e.g., Fiset et al, 2015 ). However, iron deficiency is well-known to impair growth and cause reduced appetite in both rats (Beard et al, 1995 ) and piglets (Ishaya, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of developmental differences and differences in brain morphology between rodents and humans, more and better suited animal models are needed to study the long-term cognitive effects of iron deficiency in a controlled manner. Other animal models for studying cognitive effects of iron deficiency have been suggested that more resemble the early development of humans, including guinea-pigs (Fiset et al, 2015 ), pigs (Rytych et al, 2012 ), and primates (Golub et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…On days 4 and 5, when clinical symptoms became more obvious in the NEC pigs, the difference in activity level between the 2 groups disappeared. This may relate to increased anxiety and pain in the NEC pigs along with the progression of more severe intestinal lesions [17]. Due to the unspecific nature of physical movements, and lacking knowledge about clinically relevant decreases in physical activity, more studies are required to enable precise estimates of sensitivity and specificity for physical activity as a predictor for NEC.…”
Section: Discussionmentioning
confidence: 99%